Consultation Liaison Psychiatry on Case Management of Children with Mixed Gonadal Dysgenesis Mosaicism 45X (60%) and 46XY (40%) - Jeffriey Agung; Yunias Setiawati (Health Notions, 2021)
There is an increasing in admitted patients with cases of gender identity disorder in the daycare clinic of the Child and Adolescent Psychiatry Division Dr. Soetomo, it is necessary to increase understanding and clinical ability in relation to gender identity disorders through psychiatry consultation discussion, so that management can be achieved properly and comprehensively. Disorder of sex development (DSD) is a medical disorder that is associated with an incompatibility between chromosomes, gonads, phenotypes and anatomy which is characterized by the development of external genital organs that are incompatible with whether it is male or female. Genetalia ambiguos can cause significant psychological stressors for patients or their families, where as a result of the conditions experienced, it will lead to gender dysphoria with the resulting effects, among others, in the form of anxiety, depression and low self-esteem, to affect the quality of life of children as adolescents and adults. . The method of preparing this report is a case analysis and the role of CLP which is given based on the results of the examination and references to management in the field of psychiatry of children and adolescents in cases of DSD from children aged 12 years. Conducted to strengthen the adaptation of patients to problems identifying gender development and to their families by emphasizing the importance of achieving optimal quality of life for children. The results of the case reports describe the role of Consultation Liason Psychiatry through communication and consultation between related areas of expertise, supportive psychotherapy and continuous Cognitive Behavior Therapy (CBT) techniques along with psychoeducation in families providing good development results with results in reducing patient anxiety and depression, based on children's scoring Depression Inventory (CDI) of patients with Mosaicism, Mixed Gonadal Dysgenesis (MGD). The conclusion of this case report is that the problem of psychological stressors that arise in DSD requires psychiatric assistance according to the stages of child development. The important role of psychiatrists in the management of DSD cases has been recognized and stated in the joint consensus for the treatment of individuals with DSD since 2006. CLP needs to be built because of the complexity of treatment and therapy in DSD cases, which involve subspecialty pediatric endocrinology, urology, psychiatry, gynecology, genetics, workers. social nurse and medical ethics. described in the algorithm below in the management of cases of gender dysphoric. Keywords: disorder of sex development; mixed gonadal dysgenesis; consulation liason psychiatry disorder of sex development; mixed gonadal dysgenesis; consulation liason psychiatry